Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Synergetic chemical passivation and energy level alignment via multifunctional polyurethane for high-efficiency Sb2S3 solar cells - Yifan Sun; Jiawang Che; Xiaochen Feng; Yanqing Wang; Xiang Li; Zhiping Fang; Min Fan; Dongchen Guo; Hui Dai; Chengwu Shi (Chemical Engineering Journal, 2026)

Engineering Co-N4 active sites in heptazine-porphyrin organic polymer to boost non-radical singlet oxygen generation in peroxymonosulfate activation - Xiang Li; Yu Tian; Yalong Xu; Bo Liu; Shi Zhou; Wei Jiang; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

A physics-informed neural network for continuous rice canopy thermal monitoring and forecasting from sparse UAV observations - Peng Xie; Yuan Wang; Changwen Du; Jing Che; Haitao Xiang (Computers and Electronics in Agriculture, 2026)

Assessing multidimensional changes in human settlements across urban regeneration paradigms: A case study of Wuhan, China - Meng-Tian Han; Qian Cao; Hai-Yun Xu; Xiang-Wen Deng; Lun-Che Wang; Jun Wan (Sustainable Cities and Society, 2026)

Deciphering the regional distribution patterns, petrogenetic types, and metallogenic systems of rare-metal granites in South China - Rucheng Wang; Xudong Che; Lei Xie; Zeyin Zhu; Lu Xiang; Zhimin Tang; Xinhao Duan; Yutao Lin; Shuai Huang; Jiajing Yuan (Science China Earth Sciences, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Hydrogeology of reservoirs for deep geological storage of saline coal mine drainage in groundwater Basin - Song Du; Zhan Yang; Xiao Zhang; Sheng Tao; Xiang Li; Qiaohui Che; Yinglin Fan; Yan Ding; Zhe Jiang; Yanxin Wang (Journal of Hydrology, 2026)

Effects of water table depth and fluctuations on Sphagnum palustre growth and plant community succession in subtropical mountainous Sphagnum peatlands: insights from a microcosm experiment - Ting-Ting Li; Man-Jing Tian; Jie Xu; Lun-Che Wang; Bin-Luo Li; Hui-Hui Sun; Wen-Yi Yang; Zheng-Xiang Wang (Aquatic Sciences, 2026)

Biocontrol eggplant soft rot caused by Fusarium equiseti through Bacillus amyloliquefaciens and its lipopeptides - Ping Zhou; Xilang Yang; Ziyun Xu; Xiaowei Che; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (International Journal of Food Microbiology, 2026)

Discovery and optimization of AAK1 inhibitors based on 1H-indazole scaffold for the potential treatment of SARS-CoV-2 infection - Zi Hui; Haowen Deng; Yueying Xu; Yuan Gao; Chenfeng Zhai; Nian-Dong Mao; Hao Che; Zhen Li; Yuting Zhang; Hang Zhang; Tian Xie; Xiang-Yang Ye (Molecular Diversity, 2026)

Highly isolated interlayer Co-N4 fixed by heptazine promotes peroxymonosulfate activation to selectively generate singlet oxygen - Xiang Li; Bo Liu; Shi Zhou; Chunbo Liu; Guangbo Che; Wei Jiang (Journal of Hazardous Materials, 2026)

Bioinspired multifunctional conductive hydrogel based on hydroxypropyl methyl cellulose for flexible sensors - Hongtian Yan; Haonan Gu; Shizhou Lu; Fanjun Meng; Qinglin Ma; Xiang Xing; Shihui Pan; Yuju Che (Carbohydrate Polymers, 2025)

Assessment of Egg Yolk IgY Antibodies Against Live or Inactivated Aeromonas hydrophila for Polyvalent Passive Immunization in Goldfish (Carassius auratus) - Pan Cui; Jing Chen; Huihui Xiao; Xixian Che; Shujun Sun; Zijian Ma; Juan Lu; Gaoxiao Xu; Xiang Liu (Fishes, 2025)
Egg yolk IgY antibody has significant application potential in aquaculture as a form of passive immunotherapy against various bacterial infections owing to its capacity for large-scale and cost-effective production. In this research, laying hens were immunized with live or inactivated Aeromonas hydrophila to produce IgY antibodies. Following this, experiments were carried out to assess the passive immune protection rates of the two types of IgY antibodies when used to immunize goldfish (Carassius auratus), which were then infected with A. hydrophila or Aeromonas veronii. ELISA experiments were conducted to demonstrate the interaction between the IgY antibodies and the bacteria. The kidneys of C. auratus were coated on a Luria–Bertani (LB) medium to evaluate bacterial content. The leukocyte phagocytosis was detected by a cell phagocytosis assay. The serum of C. auratus was used to assess the expression of antioxidant factors, and a qRT-PCR was conducted to evaluate the mRNA expression of inflammatory factors in visceral tissue. Furthermore, histopathology and immunofluorescence analysis were performed to evaluate the structural integrity, apoptosis, and DNA damage of visceral tissues. The results indicated that the live or inactivated A. hydrophila IgY antibodies exhibited passive immune protection rates against A. hydrophila and A. veronii and could recognize these two bacteria in vitro. Additionally, these two IgY improved the phagocytic ability of leukocytes, diminished renal bacterial concentration, and decreased the levels of antioxidant factors and mRNA expression of inflammatory factors. Meanwhile, the two IgY antibodies did not cause any pathology of the kidney, spleen, and intestine, and decreased the levels of DNA damage factor (γH2A.X) and cell apoptosis factor (p53) in renal tissue. Therefore, live and inactivated A. hydrophila IgY antibodies can resist bacterial infections, with live bacteria IgY providing greater protection than inactivated bacteria IgY. Further, A. hydrophila is an aquatic pathogen that causes minimal damage to laying hens, and the immunity of live A. hydrophila conforms to animal welfare. Altogether, live A. hydrophila IgY antibody can serve as a polyvalent passive immune vaccine candidate in aquaculture.

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Nonlinear dynamics and vibration mechanisms in air scroll compressors: A study on orbiting and fixed scroll pair - Xiao-Liang Yang; Bin Peng; Ming-Lang Che; Jian-Fei Shi; Zhi-Xiang Liao; Yu-Bo Zhang (International Journal of Refrigeration, 2025)

In situ synthesizable high-performance Ni-Fe5C2 composite catalysts for dry reforming of methane - Jiming Liu; Yaqian Li; Yuchen Che; Wenjuan Shi; Ding Wang; Ruotong Cui; Xiang Feng; Jinhong Zhang; Huie Liu; Yuanyu Tian (Chemical Engineering Journal, 2025)

Insight into VOCs source profiles by machine learning: Role of commonalities in synergistic pollution controls - Shuwei Zhang; Song Gao; Bo Wang; Zhukai Ning; Lingning Meng; Ming Hu; Xiang Che; Zheng Jiao (Journal of Hazardous Materials, 2025)

Polyvalent immunoprotection of protein, DNA and IgY antibody vaccines of Vibrio fluvialis outer membrane protein VF08100 in fish - Huihui Xiao; Saixing Duan; Pan Cui; Jing Chen; Xixian Che; Juan Lu; Juan Wang; Guoping Zhu; Yong Liu; Xiang Liu (Fish & Shellfish Immunology, 2025)

Development and characterization of novel wood-based composite materials for solar-powered atmospheric water harvesting: A machine intelligence supported approach - Xingying Zhang; Yangyang Xu; Shenjie Han; Xiang Weng; Wenbo Che; Kongjie Gu; Ying Guan; Youming Yu; Derek Hao; Junfeng Hou (Journal of Cleaner Production, 2025)

Olaparib research update: mechanism, structure and clinical trials - Hao Che; Li-Wei Wang; Xiang-Yang Ye; Xingrui He (Medicinal Chemistry Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Applicability of Different Indices for Delineating the Boundary of Arid Region: A Case Study in Northwestern China - Xue Peng; Xiang Li; Yingyibing Shen; Xuehua Che; Shipei Dong; Zhuolun Li (Journal of Earth Science, 2025)

Whole-pathway stimulation of anthocyanin biosynthesis by UDP-glycose: Flavonoid glycosyltransferase gene (UFGT) providing new insights into natural product development based on plant cell factory - Gongti Lai; Liyuan He; Junxuan Lin; Aolin Guo; Qiuxia Que; Jianmei Che; Xuefang Guan; Jiang Xiang; Chengchun Lai (Food Bioscience, 2024)

The Multifaceted Roles of Hippo-YAP in Cardiovascular Diseases - Hao Wu; Yan-Nan Che; Qi Lan; Yi-Xiang He; Ping Liu; Ming-Tai Chen; Li Dong; Meng-Nan Liu (Cardiovascular Toxicology, 2024)

Nondestructive estimation of specific macroelement contents in thalli of the red macroalga Pyropia yezoensis using hyperspectral imaging - Shuai Che; Lan Wu; Zhen-Dong Wang; Lin Tian; Guo-Ying Du; Yun-Xiang Mao (Journal of Applied Phycology, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

Boosting photocatalytic activity in ternary lamellar hierarchical structured ZnFe2O4/polymeric carbon nitride by constructing an electronic bridge - Youhai Zhao; Zishuang Guo; Yucheng Wang; Martin Birkett; Xiao Xiang; Chengang Zhang; Yaran Jin; Guangbo Che; Haiwang Wang; Chunbo Liu; Terence Xiaoteng Liu; Jian Qi (Journal of Environmental Chemical Engineering, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

Exosomes Derived from Adipose Stem Cells Enhance Angiogenesis in Diabetic Wound Via miR-146a-5p/JAZF1 Axis - Dehui Che; Xinjian Xiang; Juan Xie; Zenghong Chen; Qiong Bao; Dongsheng Cao (Stem Cell Reviews and Reports, 2024)
Chronic trauma in diabetes is a leading cause of disability and mortality. Exosomes show promise in tissue regeneration. This study investigates the role of exosomes derived from adipose stem cells (ADSC-Exos) in angiogenesis. MiRNA-seq analysis revealed significant changes in 47 genes in human umbilical vein endothelial cells (HUVECs) treated with ADSC-Exos, with miR-146a-5p highly expressed. MiR-146a-5p mimics enhanced the pro-angiogenic effects of ADSC-Exos, while inhibitors had the opposite effect. JAZF1 was identified as a direct downstream target of miR-146a-5p through bioinformatics, qRT-PCR, and dual luciferase assay. Overexpress of JAZF1 resulted in decreased proliferation, migration, and angiogenic capacity of HUVECs, and reduced VEGFA expression. This study proposes that ADSC-Exos regulate angiogenesis partly via the miR-146a-5p/JAZF1 axis. Graphical Abstract

Trajectory Planning for Cooperative Double Unmanned Surface Vehicles Connected with a Floating Rope for Floating Garbage Cleaning - Mengdi Zhang; Xiang Zheng; Jianhua Wang; Zijun Pan; Wenbo Che; Haozhu Wang (Journal of Marine Science and Engineering, 2024)
Double unmanned surface vehicles (DUSVs) towing a floating rope are more effective at removing large floating garbage on the water’s surface than a single USV. This paper proposes a comprehensive trajectory planner for DUSVs connected with a floating rope for cooperative water-surface garbage collection with dynamic collision avoidance, which takes into account the kinematic constraints and dynamic cooperation constraints of the DUSVs, which reflects the current collection capacity of DUSVs. The optimal travel sequence is determined by solving the TSP problem with an ant colony algorithm. The DUSVs approach the garbage targets based on the guidance of target key points selected by taking into account the dynamic cooperation constraints. An artificial potential field (APF) combined with a leader–follower strategy is adopted so that the each USV passes from different sides of the garbage to ensure garbage capturing. For dynamic obstacle avoidance, an improved APF (IAPF) combined with a leader–follower strategy is proposed, for which a velocity repulsion field is introduced to reduce travel distance. A fuzzy logic algorithm is adopted for adaptive adjustment of the desired velocities of the DUSVs to achieve better cooperation between the DUSVs. The simulation results verify the effectiveness of the algorithm of the proposed planner in that the generated trajectories for the DUSVs successfully realize cooperative garbage collection and dynamic obstacle avoidance while complying with the kinematic constraints and dynamic cooperation constraints of the DUSVs.

N atoms regulate heterogeneous crystal phase engineering of mesoporous magnetic FexN nanofibers to promote electromagnetic wave dissipation of magnetic composite aerogel absorbers - Wanjia Li; Wangchang Li; Zengbao Ma; Yue Kang; Ting Zou; Yu Lei; Yao Ying; Wenbo Xiang; Jing Yu; Jingwu Zheng; Liang Qiao; Juan Li; et al. (Chemical Engineering Journal, 2024)

Response of soil physicochemical properties, soil nutrients, enzyme activity and rice yield to rice straw returning in highly saline-alkali paddy soils - Weikang Che; Junlong Piao; Qian Gao; Xuebin Li; Xiang Li; Feng Jin (Journal of Soil Science and Plant Nutrition, 2023)

FPGA–accelerated CNN for real-time plant disease identification - Yuexuan Luo; Xiang Cai; Jiandong Qi; Dongdong Guo; Wenqing Che (Computers and Electronics in Agriculture, 2023)

Application of peanut shell biochar increases rice yield in saline-alkali paddy fields by regulating leaf ion concentrations and photosynthesis rate - Junlong Piao; Weikang Che; Xiang Li; Xuebin Li; Chengbo Zhang; Qingshu Wang; Feng Jin; Shuang Hua (Plant and Soil, 2023)

Brain structural connectivity sub typing in unilateral temporal lobe epilepsy - Zhensheng Li; Che Jiang; Wei Xiang; Zijuan Qi; Quwen Gao; Kairun Peng; Jian Lin; Wei Wang; Weimin Wang; Bingmei Deng (Brain Imaging and Behavior, 2022)

Bacterial community structure upstream and downstream of cascade dams along the Lancang River in southwestern China - Xia Luo; Xinyi Xiang; Guoyi Huang; Xiaorui Song; Peijia Wang; Yuanhao Yang; Kaidao Fu; Rongxiao Che (Environmental Science and Pollution Research, 2020)
Extensive construction of dams by humans has caused alterations in flow regimes and concomitant alterations in river ecosystems. Even so, bacterioplankton diversity in large rivers influenced by cascade dams has been largely ignored. In this study, bacterial community diversity and profiles of seven cascade dams along the720 km of the Lancang River were studied using Illumina sequencing of the V3-V4 hypervariable region of the 16S rRNA gene. Spatiotemporal variations of bacterial communities in sediment and water of the Gongguoqiao hydroelectric dam and factors affecting these variations were also examined. Microbial diversity and richness in surface water increased slightly from upstream toward downstream along the river. A significant positive correlation between spatial distance and dissimilarities in bacterial community structure was confirmed (Mantel test, r = 0.4826, p = 0.001). At the Gongguoqiao hydroelectric dam, temporal differences in water overwhelmed spatial variability in bacterial communities. Temperature, precipitation, and nutrient levels were major drivers of seasonal microbial changes. Most functional groups associated with carbon cycling in sediment samples decreased from winter to summer. Our findings improve our understanding of associations, compositions, and predicted functional profiles of microbial communities in a large riverine ecosystem influenced by multiple cascade dams.

Thioredoxin-interacting protein mediates mitochondrion-dependent apoptosis in early brain injury after subarachnoid hemorrhage - Yidan Liang; Xudong Che; Qing Zhao; Rami Darwazeh; Hongxia Zhang; Dengzhi Jiang; Jun Zhao; Xiang Xiang; Wang Qin; Liu Liu; Zhaohui He (Molecular and Cellular Biochemistry, 2019)

Aerosol optical properties and radiative impacts in the Pearl River Delta region of China during the dry season - Boru Mai; Xuejiao Deng; Zhanqing Li; Jianjun Liu; Xiang’ao Xia; Huizheng Che; Xia Liu; Fei Li; Yu Zou; Maureen Cribb (Advances in Atmospheric Sciences, 2018)

Optical and radiative properties of aerosols during a severe haze episode over the North China Plain in December 2016 - Yu Zheng; Huizheng Che; Leiku Yang; Jing Chen; Yaqiang Wang; Xiangao Xia; Hujia Zhao; Hong Wang; Deying Wang; Ke Gui; Linchang An; Tianze Sun; et al. (Journal of Meteorological Research, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

A wireless sensor network-based monitoring system with dynamic convergecast tree algorithm for precision cultivation management in orchid greenhouses - Joe-Air Jiang; Chien-Hao Wang; Min-Sheng Liao; Xiang-Yao Zheng; Jen-Hao Liu; Cheng-Long Chuang; Che-Lun Hung; Chia-Pang Chen (Precision Agriculture, 2016)

Mapping Water Vulnerability of the Yangtze River Basin: 1994–2013 - Fengyun Sun; Wenhui Kuang; Weining Xiang; Yue Che (Environmental Management, 2016)

Causal nexus between energy consumption and carbon dioxide emission for Malaysia using maximum entropy bootstrap approach - Sehrish Gul; Xiang Zou; Che Hashim Hassan; Muhammad Azam; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Microbial Diversity and Succession in the Chinese Luzhou-Flavor Liquor Fermenting Cover Lees as Evaluated by SSU rRNA Profiles - Ke Li; Qing Zhang; Xiao-Ting Zhong; Bi-Hong Jia; Chun-Hong Yuan; Sen Liu; Zhen-Ming Che; Wen-Liang Xiang (Indian Journal of Microbiology, 2013)

Microbial succession in the traditional Chinese Luzhou-flavor liquor fermentation process as evaluated by SSU rRNA profiles - Wenliang Xiang; Ke Li; Seng Liu; Yage Xing; Mingyuan Li; Zhenming Che (World Journal of Microbiology and Biotechnology, 2013)

Myceligenerans salitolerans sp. nov., a halotolerant actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Nan Wu; Shu-Kun Tang; Zhen-Ming Che; Xiang-Gui Chen (Extremophiles, 2013)

Assessing the health of an urban stream: a case study of Suzhou Creek in Shanghai, China - Yue Che; Kai Yang; Enuo Wu; Zhaoyi Shang; Weining Xiang (Environmental Monitoring and Assessment, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

Isolation and performance evaluation of halotolerant phosphate solubilizing bacteria from the rhizospheric soils of historic Dagong Brine Well in China - Wen-liang Xiang; Hua-zhong Liang; Sen Liu; Fan Luo; Jie Tang; Ming-yuan Li; Zhen-ming Che (World Journal of Microbiology and Biotechnology, 2011)